Dietary assessment of schoolchildren: is food record a valid method? (Research, Society and Development, 2021)
Objective: To verify the relative validity of 24-hour Dietary Recall (R24h) as an assessment tool of schoolchildren´s food intake.  Methods: A cross-sectional study of 41 students of a big Brazilian urban center, with a mean age of 0.25–8.35 years and 22% had excess weight. The R24h was applied a day after direct observation of intake (reference method). Weight and height were measured and the participants were categorized according to nutritional status (excess weight or not). The median energy, macronutrients (carbohydrate, protein and lipid) and micronutrients intake (iron, calcium and vitamin A) was compared. The Mann-Whitney test was conducted. Also, Spearman and kappa correlation coefficients were calculated. Results: Median energy and nutrient intake irrespective of nutritional status was similar according to the test and reference methods. Higher correlations were found for protein (r= 0.87) and iron (r = 0.71) but the values were more accentuated among students with excess weight. Kappa coefficient was low for vitamin A, moderate for carbohydrate and lipid, good for iron and protein, and very good for energy. Conclusions: R24h is a valid method for the assessment of food intake among schoolchildren. It is a potential practical and economical food assessment method, which can find application in epidemiological studies focused on food intake in early life.